Burden of All Cancers Along With Attributable Risk Factors in China From 1990 to 2019: Comparison With Japan, European Union, and USA - Yang, Xiaorong; Chen, Hui; Sang, Shaowei; Chen, Hao; Li, Lanbo; Yang, Xiaoyun (Frontiers in Public Health, 2022)
Background Understanding the epidemiological characteristics of various cancers can optimize the prevention and control strategies in the national cancer control plan. This study aimed to report the burden differences, pattern trend, and potential risk factors of all neoplasm types in China in recent 30 years, and further compared with top economies in the world. Methods The disability-adjusted life-years (DALYs) and age-standardized DALY rate (ASDR) of all neoplasms with the attributable risk factors from 1990 to 2019 in China, Japan, European Union, USA, and the world were extracted from the Global Burden of Disease Study 2019. The temporal trend analysis was estimated using the joinpoint regression model. Results In 2019, about 251.4 million DALYs worldwide were caused by all neoplasms, and nearly 26.9% (67.5 million DALYs) occurred in China with the ASDR in 2019 of 342.09/10 000, which was higher than European Union (334.25/10 000), USA (322.94/10 000), and Japan (250.36/10 000). Although the cancer burden of the colorectum, non-Hodgkin lymphoma, oral cavity, ovary, and kidney in China was lower than in Japan, European Union and USA, the corresponding ASDR gradually increased in China over the past 30 years, but declined in the three developed areas. Around 46.29% of overall neoplasms DALYs in China in 2019 were attributed to 22 identified risk factors, and the specific risk attributable-fraction for several neoplasm types varied greatly in these regions. Conclusion The ASDR of cancers of the lung, colorectum, pancreas, non-Hodgkin lymphoma, oral cavity, ovary, kidney, and chronic lymphoid leukemia increased in China compared to 30 years ago. With the population aging and the social transformation in China, the increasing burden of neoplasms and the changing spectrum of neoplasms suggest that effective comprehensive prevention and treatment measures should be adopted to reduce the burden, including public health education, strict tobacco-control policy, healthier lifestyles, along with expanding vaccination programs and early cancer screening.